Computational Thinking and Social Science : combining programming, methodologies and fundamental concepts - Nelimarkka, Matti (Los Angeles : SAGE, 2023)
"Taking a blended approach to computational social science, this book helps you understand the fundamentals of what is is alongside the techniques for doing it. It is a practical, step-by-step guide into how, why and when computational social sciences should be used in the first place. It will improve: Your ability to understand challenges and benefits that computational methods provide within social science. Your computational thinking and basics in programming to understand how the processes work. You translation from research problems into algorithms. Your use of computational tools, from a range of applications without going into advanced technical detail. Computational Thinking and Social Science focuses on helping you understand and design computational research that addresses social science problems regarding your interests. With condensed summaries, key concepts, exercises accompanies by sample code and boxed examples of computational methods within social science research throughout each chapter, this book will allow you to delve deeper into context of coding and why it exists"--
Includes bibliographical references (pages [333]-348) and index.
Keywords: Social sciences -- Methodology -- Data processing